Asuhan Keperawatan Jiwa Pada Pasien Dengan Resiko Perilaku Kekerasan Di Wisma Nuri RSJ Prof. Dr. HB Sa’anin Padang Tahun 2026 - Laura Aprilia Suja; Dwi Happy Anggia Sari; Ramaita Ramaita; Vivi Yuderna (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
The prevalence of mental disorders worldwide according to WHO in 2023 there were 970 million individuals in various parts of the world who experienced mental disorders.This data has increased in 2024 to exceed 1.1 billion people. This increase in prevalence strongly confirms that the burden on mental health in society at the global level is getting heavier. The risk of violent behavior is a condition where a person commits an action that can be physically harmful, either to themselves, others or the surrounding environment.  Based on initial data collection obtained from Prof. Dr. HB. Sa’anin Padang Mental Hospital, the second most common problem in 2025 was the risk of violent behavior with a total of 159 patients. This study aims to implement Mental Nursing Care for Patients with Risk of Violent Behavior at Wisma Nuri Prof. Dr. HB. Sa’anin Padang Mental Hospital. The implementation of Nursing Care for Patients with Risk of Violent Behavior was carried out on February 4 to February 10, 2026 with a visit of six days of meetings. This Scientific Paper method is in the form of a case study. The results of the provision of Mental Health Nursing Care showed that patients with a risk of violent behavior were able to control the RPK independently by using implementation strategies (SP), namely SP 1 to SP 4. In this study, it is expected that patients will be able to control the risk of violent behavior independently and that the signs and symptoms of RPK will decrease.